(untitled) (Actualizaciones en Sida e Infectología, 2023)
This quasi-experimental study was developed in a public hospital with the goal of reducing the impact of antimicrobial resistance through an infection prevention and antimicrobial stewardship program. The following measures were implemented: surveillance of colonization and infection by carbapenemase-producing Enterobacteriaceae (CPE); surveillance and preventive measures for urinary catheter-associated infections (UTIs); surveillance and interventions for hand hygiene; local guidelines for treatment of infectious diseases with compliance and antibiotic (ATB) consumption metrics. Results: comparing the pre-intervention and post-intervention period, CPE rate in clinical samples 1.1 to 0/patient days, incidence rate ratio (IRR): 0.00, p: 0.033 and colonization of 3.3 to 0.61/days patient, IRR: 0.18, p-value: 0.5. UTI rate 8.9 to 7.2/1000 days urinary catheter IRR: 0.81, p 0.5. Hand Hygiene compliance: 77.5% to 70.38%, p 0.0067. ATB consumption: 376.24 to 176.82 DDD, 53% decrease. Compliance to guidelines in ATB selection: 57.1% to 95.4% p 0.00031, duration of ATB from 92.8% to 98.4% p 0.16, and adequacy to microbiological rescue of 57.1% at 100%, p <0.01. Conclusion: it is possible to reduce CPE infections, the consumption of antimicrobials and optimize their use in a public hospital in a country with medium/low resources through a program with basic and tailored measures.